Perlindungan Konsumen terhadap Konsumen dari Penjualan Beras Curah Tanpa Merek: Consumer Protection for Consumers from the Sale of Unbranded Bulk Rice - Pratama, Astrid Amelia Putri; Yumi, Meiliana; Cahayu, Elan; Nirfansyah, Taufik (Jurnal Hukum Bisnis, 2026)
Certainty of Distribution Unbranded bulk rice in traditional markets and unofficial distribution channels remains common in Indonesia, raising legal issues regarding consumer protection. Rice products traded without brand identity, labels, composition, or quality information may harm consumers by depriving them of the right to receive accurate, clear, and honest information about the goods they consume. This study aims to analyze the legal protections for consumers in relation to the practice of selling unbranded bulk rice, and the responsibilities of business actors under consumer protection law and food regulations. The research method used is a normative juridical approach, with a statutory and conceptual perspective. Data were obtained through a literature review of relevant regulations, books, and journal articles and were then analyzed qualitatively and descriptively. The results of the study indicate that the sale of unbranded bulk rice may violate business actors' obligations regarding labeling, quality standards, and transparency of product information. Consumers are in a weak position due to information asymmetry and limited oversight at the distribution level. Legal protection is available through preventive and repressive mechanisms, including labeling obligations, government supervision, administrative sanctions, and compensation claims. However, the effectiveness of protection remains constrained by implementation challenges, particularly in the small-scale trade sector. Therefore, it is necessary to strengthen supervision, educate business actors and consumers, and enforce the law consistently to ensure legal certainty and public food safety.